Analyzing the development of university English students’ speaking fluency - Aziez, Feisal; Nita, Alfia; Istikharoh, Lutfi; Sotlikova, Rimajon (English Education Department, Universitas Islam Indonesia, 2024)
The development of speaking fluency is a critical aspect of English language learning, particularly for non-native speakers. This study investigates the progress of university English learners in improving their speaking fluency, focusing on two key measures: the length of silent pauses and the use of pause fillers. A quantitative approach was employed, utilizing a pre-experimental design with 61 second-year students from two private universities, one in Indonesia and one in Uzbekistan. These students were enrolled in a speaking course at their respective universities, and the study served as an evaluative measure for the course. Data were collected through speaking tasks administered at the beginning and end of the course, where students delivered five-minute monologues on topics related to professional communication, specifically the creation of a startup company. The findings revealed a significant reduction in silent pauses, indicating an improvement in fluency, while the use of pause fillers showed minimal change.